Adjective constructions denoting appearance of a person - Latun, A. B. (Видавництво НДУ ім. М. Гоголя, 2019)
The article is devoted to the analysis of adjective constructions denoting appearance of a person in Internet news articles which are represented by immediate, modified and extended ones. The conducted investigation reveals, that the group of constructions expressing appealing appearance is more numerous due to the author’s intention to attract readers’ attention. Immediate adjective constructions state a certain characteristic in the appearance of people, either positive or negative while modified and extended ones are used to emphasize different shades of attractiveness or unattractiveness of people. The constructions under analysis occur in different syntactical positions, namely of the subject, the predicative and the object, and can be a part of compound predicate. In the immediate, modified and extended units, the adjectives are represented by compound, denominal and determining items as well as by participles.
Keywords: adjective construction; immediate construction; modified construction